Modular Information Management: Using AUSTLANG to Enhance the Classification of Australian Indigenous Knowledge Resources. Issue 4 (2nd October 2021) - Miniter, Amy; Vo-Tran, Huan
ABSTRACT: This research explores the potential for AUSTLANG – a database of Australian Indigenous languages – to enhance the identification of Australian Indigenous languages in MAchine Readable Cataloguing (MARC) bibliographic records. At present, it is acknowledged in the discipline of Library and Information Sciences (LIS) that material relating to Indigenous peoples are improperly and/or insensitively classified using mainstream library systems such as Dewey Decimal Classification. AUSTLANG was approved as a MARC language source code in November 2018 and has given libraries the ability to identify Australian Indigenous languages with standardised, culturally sensitive identifiers. The following research considers the variety of orthographies, codes and synonyms available for a sample of four Australian Indigenous languages as listed in AUSLANG and contrasts these with the single, authoritative AIATSIS reference names and codes contributed by the database. This research also considers how AUSTLANG can contribute to the classification of Indigenous Knowledge resources. Currently there is only a small body of technical information available on AUSTLANG and little focussed academic research, making it difficult to ascertain the success and characteristics of its implementation. This research represents an exploratory academic contribution and calls for a wider research effort.